Extremely High-frequency Therapy in the Complex Treatment of Pneumonia in Patients with Burn and Inhalation Trauma - V. A. Shchyotkin; E. A. Chukina; T. G. Spiridonova; N. V. Borovkova; E. A. Beresneva; E. A. Zhirkova; M. V. Storozheva (Неотложная медицинская помощь, 2019)
Background. The improvement of treatment tactics for nosocomial pneumonia in patients with burn and inhalation trauma is a relevant issue due to the frequency of this complication, which develops at any stage of treatment and aggravates the course of the underlying disease.Aim of study. To evaluate the effectiveness of extremely high frequency therapy (EHFT) in the complex treatment of pneumonia in patients with burn and inhalation injury.Material and methods. The results of extremely high-frequency therapy (EHFT) was compared, studying 23 burn patients with complex EHFT and 30 patients without EHFT.Results. EHFT reduces the signs of endogenous toxemia, as evidenced by a statistically significant decrease in elevated concentrations of dead leukocytes in venous blood from 147-106/L (98; 363-106/L) to 81.8-106/L (72; 150-106/L) (p=0.041, Wilcoxon test) on day 6-8 (after 5-6 procedures), whereas in the comparison group, on the contrary, an increase in the dead cells from 121-106/L (66; 210-106/L) up to 137.4-106/L (116; 207-106/L) was observed. When comparing this indicator in two groups on day 6-8 from the onset of pneumonia, a statistically significant difference was found (p=0.021, Mann-Whitney). The term of managing pneumonia in patients receiving EHFT was significantly shorter than in the comparison group, 18 (13; 23) versus 21 (18; 27) days (p=0.020, Mann-Whitney).Conclusion. EHFT reduced intensity of endogenous toxicosis and inflammation, approaching pneumonia relief for 3 days.